2014 IEEE Industry Application Society Annual Meeting 2014
DOI: 10.1109/ias.2014.6978420
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plug-in Electric Vehicle battery charging on a distribution system

Abstract: Plug-in Electric Vehicles (PEV) battery chargers are mostly connected to the low-voltage grid for charging. Their increased penetration coupled with uncoordinated charging could impact the distribution system in terms of unbalanced voltage and transformer overloading. Although PEV battery charging is increasing, impact on the distribution system is not fully investigated. This paper focuses on unbalanced voltage caused by uneven distribution of PEV penetration among the phases. Using real data provided by util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Of the MV and LV networks, the voltage profile impact is more pronounced on the LV network since they are directly connected to the EVs charging stations; this is clear from the [133] and [119]. Also, coordinated charging displayed superior performance over uncoordinated charging as a function of EVs penetration rate for voltage profile factor in [116], [118], [135]- [142].…”
Section: B Voltage Profile and Phase Unbalance Impactmentioning
confidence: 98%
See 1 more Smart Citation
“…Of the MV and LV networks, the voltage profile impact is more pronounced on the LV network since they are directly connected to the EVs charging stations; this is clear from the [133] and [119]. Also, coordinated charging displayed superior performance over uncoordinated charging as a function of EVs penetration rate for voltage profile factor in [116], [118], [135]- [142].…”
Section: B Voltage Profile and Phase Unbalance Impactmentioning
confidence: 98%
“…The outcome outlined in [148] showed that a severe unbalance condition arose, which needs special consideration upon adopting EV charging. Also, a real 12.47 kV network was studied in [142] to investigate unbalance voltage effects under many EVs penetration rates ranging from 10 % to 80 % along with single and double AC level 1 and AC level 2 charger types. The authors in [119], [133] found that fast charging shall not be used at LV side, as it impacts voltage balance factor badly, and this can be alleviated by dedicating a separate circuit for the fast charger.…”
Section: B Voltage Profile and Phase Unbalance Impactmentioning
confidence: 99%
“…Frente ao inevitável crescimento da frota de veículos elétricos, alguns pontos precisam ser melhor explorados, pois nem toda tecnologia inovadora surge sem causar algum tipo de impacto negativo. No caso dos veículos elétricos, o impacto negativo mais imediato tende a ser o aumento de demanda que podem implicar no sistema elétrico de potência, promovido pelo aumento de consumo de energia elétrica em residências, estabelecimentos públicos, postos de recarga espalhados em lugares estratégicos, etc (Richardson et al, 2010;Bunga et al, 2014;e W. G. Morsi, 2017;Neagoe-Ştefana et al, 2014). Sendo ideal, de um ponto de vista inicial, que esses veículos sejam recarregados durante baixa demanda residencial, durante a noite (Clement-Nyns et al, 2010).…”
Section: Impactos Dos Vesunclassified
“…The main advantage of using renewable energy is to mitigate the power demand increasing of EVs chargers from the main grid. The expected widespread of EV single-phase chargers' adaption will add a significant unbalanced load among the main grid phases mainly at distribution networks [7]. The unbalanced operation of the distribution network will result in overloading the distribution transformer, which also leads to a serious increase in losses and voltage unbalance [8], [9].…”
Section: Introductionmentioning
confidence: 99%